Philippine MBA Program: A Vision of the Academe and Industry - Nangoy, Stanley (JIU (Jurnal Ilmiah Unklab); Volume 3 No. 1, 2000 JIU UNKLAB, 2000)
MBA program has been recognized as one of the most successful business and management education programs in the 20 th century. Is the MBA program still considered important in the 21 st century as it was in the 20 th century? This study provides some insights from the Philippines’ Academe and Industry about the prospects of the 21 st century MBA programs in the Philippine business environment that will be greatly influenced by information technology and global business orientation, and the MBA program should concentrate on an entrepreneurship, international business, and information technology.